Implications of Covid-19 on crisis management, from the perspective of Moroccan employees - Laassila, Yasmine (My University, 2022)
The unexpected emergence of the Coronavirus at the end of the year 2019 as a global health crisis had big and obvious impacts on our lives in all its aspects. Consequently, businesses had to adapt to these impacts in order to survive. The purpose of this thesis research is to determine the practices that crisis management teams have used in order to manage Covid-19 within their organizations in Morocco and the impacts that these practices have had and are still having on the job satisfaction of their employees. A conceptual framework has been set in place for this study in order to measure to what extent does working from home, the adoption of digital transformation, performance management and employee training affect job satisfaction of employees in Morocco, which is the main research question of this study. This research follows a survey research design through which data has been collected from 187 respondents. Using this data, a partial least squares analysis was conducted in order to test our hypotheses and validate them. Results of this analysis show that there is in fact a strong correlation between performance management and employee training on job satisfaction of employees during the pandemic, while work from home has a positive partial mediation impact on the relationship between digital transformation and job satisfactions. They imply that work from home, training, digital transformation and performance management have strong positive impacts on the job satisfaction of employees during the Coronavirus pandemic, at least according to the Moroccan employees that were surveyed during this study. These findings can be used to customize crisis management plans of Covid-19 in Morocco and even design precautionary ones for potential threats and crises. This can lead to a better future response to these plans. Management – Human resources – Coronavirus – Working from home – Employee development - Digital transformation - Performance management IV

Koronavirüsün 2019 yılı sonunda küresel bir sağlık krizi olarak beklenmedik bir şekilde ortaya çıkması, tüm yönleriyle hayatımızda büyük ve bariz etkiler yarattı. Sonuç olarak, işletmeler hayatta kalabilmek için bu etkilere uyum sağlamak zorunda kalmaktadır. Bu bildirinin amacı, kriz yönetim ekiplerinin Fas'taki kuruluşlarında Covid-19'u yönetmek için kullandıkları uygulamaları ve bu uygulamaların çalışanlarının iş tatmini üzerindeki etkilerini ve halen devam etmekte olan etkilerini belirlemektir.Bu çalışmanın ana araştırma sorusu olan Fas'ta evden çalışmanın, dijital dönüşümün benimsenmesi, performans yönetimi ve çalışan eğitiminin çalışanların iş tatminini ne ölçüde etkilediğini ölçmek için bu çalışma için kavramsal bir çerçeve oluşturulmuştur. kağıt. Bu araştırma, 187 katılımcıdan verilerin toplandığı bir anket araştırması tasarımını takip etmektedir. Bu veriler kullanılarak hipotezlerimizi test etmek ve doğrulamak için kısmi en küçük kareler analizi yapılmıştır. Bu analizin sonuçları, performans yönetimi ile pandemi sırasında çalışanların iş tatmini konusunda çalışan eğitimi arasında aslında güçlü bir ilişki olduğunu gösterirken, evden çalışmanın dijital dönüşüm ile iş tatminleri arasındaki ilişki üzerinde olumlu bir kısmi aracılık etkisi olduğunu gösteriyor. En azından bu çalışma sırasında ankete katılan Faslı çalışanlara göre, evden çalışma, eğitim, dijital dönüşüm ve performans yönetiminin korona virüs pandemisi sırasında çalışanların iş tatmini üzerinde güçlü olumlu etkileri olduğunu ima ediyorlar. Bu bulgular, Fas'ta Covid-19'un kriz yönetimi planlarını özelleştirmek ve hatta potansiyel tehditler ve krizler için ihtiyati planlar tasarlamak için kullanılabilir. Bu, bu planlara gelecekte daha iyi yanıt verilmesine yol açabilmektedir.
Keywords: Business; Human Resources Management - Crisis Management - Coronavirus - Work from home İnsan Kaynakları Yönetimi - Kriz Yönetimi - Koronavirus - Evden çalisma; İşletme